2006
DOI: 10.7577/nibr/samarbeidsrapport/2006/4
|View full text |Cite
|
Sign up to set email alerts
|

Samfunnsøkonomiske effekter av universell utforming

Abstract: Rapporten analyserer den samfunnsøkonomiske lønnsomheten av universell utforming. Det vurderes hvilke nytte-og kostnadsvirkninger som bør inngå i eventuelle samfunnsøkonomiske lønnsomhetsanalyser. Rapporten viser at det kan vaere vanskelig å tallfeste nyttekomponenter både pga. at det er vanskelig eller umulig å måle noen av effektene og manglende data når det gjelder komponenter som i prinsippet kan måles. Når det gjelder måling av kostnadskomponentene er problemene knyttet til at enhetspriser ved anbud ikke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Frode Kann, Bjørg Langset and Per Medby Socio-economic cost of accidentals falls on stairs in residential buildings NIBR Report: 2010:23 The project explores the economic cost of accidental falls and how installing a lift could reduce accident frequency. The background for the project is an earlier report on the socio-economic gains of universal design (Medby et al 2006). Some of the measures required for implementing the policy to increase the number of universally designed homes are likely to be relatively expensive, not least when the measure includes the installation of lifts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frode Kann, Bjørg Langset and Per Medby Socio-economic cost of accidentals falls on stairs in residential buildings NIBR Report: 2010:23 The project explores the economic cost of accidental falls and how installing a lift could reduce accident frequency. The background for the project is an earlier report on the socio-economic gains of universal design (Medby et al 2006). Some of the measures required for implementing the policy to increase the number of universally designed homes are likely to be relatively expensive, not least when the measure includes the installation of lifts.…”
Section: Discussionmentioning
confidence: 99%
“…The problems associated with estimating the benefits could therefore result in net benefits being underestimated. Medby et al (2006) found that many of the benefits of universal design could be estimated if the data were gathered. One benefit which the report believed could be quantified was reduced costs of resulting from a lower incidence of accidental falls on stairs.…”
Section: Discussionmentioning
confidence: 99%